COST ANALYSIS AND FACTORS THAT INFLUENCE COST OF HEART FAILURE TREATMENT OF HOSPITALIZED PATIENT IN RSUD SLEMAN YOGYAKARTA FOR PERIOD 2009 - Herlin Surlita; Satibi Satibi; Ali Ghufron Mukti (Faculty of Pharmacy, Universitas Gadjah Mada)
Heart failure is a complex clinical syndrome and the risk of high morbidity and mortality in the population. HeartFailure is a disease requiring long therapy, so cost for heart failure treatment is very high.This study design was descriptive non experimental. Data was collected retrospectively. Data was analyzedby descriptive quantitative, and statistical method using correlation analysis. Data was classified based on costingsystem and number of comorbid.The mean and proportion of overall total costs of heart failure on non poor patients were greater than poorpatients and its value increases along with increasing number of comorbid. Laboratory cost dominate total cost for poor group without or with comorbid. While for non poor group was laboratory cost on patient without comorbid (29,80%) and with 1 comorbid (25,93%), on patient with 2 comorbid was medicine cost (21,99%) and onpatient with more than 2 comorbid was hospitalization cost (23,21%). Correlation test among patient characteristicindicating that six variable had significant correlation. Correlation test using a multivariate analysis showed thatvariable which significantly correlated with total cost on poor group was number of comorbid, and on non poorgroup was number of comorbid and LOS. Keyword : Heart failure, cost, type of costing system, number of comorbid